Geology of the Asinara Island (Sardinia, Italy) - R. Carosi; C. Montomoli; D. Iacopini; A. Petroccia; M. Simonetti; G. Oggiano (Journal of Maps, 2024)
Understanding how the lithosphere accommodates deformation along oblique convergent plate boundaries is an important issue for unveiling orogenic belt exhumation. The Variscan belt exposed in Sardinia represents an area where it is possible to investigate the inner part of this orogen and a km-scale transpressive shear zone, i.e. the Posada-Asinara shear zone, that drove the exhumation of the metamorphic core of the belt. Even though the Asinara island offers very good exposure of main tectonic units building up the Variscan belt of Sardinia, a detailed geological map of the island is still lacking, due to a former limitation of access that lasted for many years. In this contribution, we compile a new 1:25.000 geological-structural map of the entire Asinara island useful to better understand this key sector of the Variscan belt in Sardinia.